Aldosterone Glucuronide, an Important Biomarker: Synthesis and Structure Elucidation of Novel Isomers. Issue 67 (19th November 2020) - Guha, Somraj; Senthilkumar, Soundararasu; Voß, Edgar; Tietze, Lutz F.
Abstract: Aldosterone 1 is a mineralocorticoid, it has great influence on the blood pressure and its glucuronide is an important marker for the detection of several diseases. Here, we describe the chemical synthesis of different aldosterone‐18‐ and 20‐glucuronides. Reaction of trimethylsilyl 2, 3, 4‐tri‐ acetyl‐1‐β‐glucuronic acid methyl ester 5 b and aldosterone diacetate 11 in the presence of TMSOTf gave the 18‐α‐glucuronide 9 a . The 18‐β‐glucuronide 15 b and the 20‐β‐glucuronide 16 b could be obtained by reaction of methyl 2, 3, 4‐tri‐ O ‐isobutyryl‐1α‐glucuronate trichloroacetimidate 14 and aldosterone 21‐acetate 8 in the presence of TMSOTf or BF3 ⋅OEt2 . Finally, reaction of aldosterone 21‐acetate 8 and methyl 2, 3, 4‐triacetyl‐1α‐glucuronate trichloroacetimidate 19 in the presence of TMSOTf gave the corresponding methyl 18‐β‐triacetylglucuronate 9 b, which was transformed into the desired aldosterone‐18‐β‐glucuronide 3 by two enzyma‐ tic transformations. Abstract : A biomarker : ( 18R )‐Aldosterone‐18‐β‐d ‐glucuronide (1) is an important biological marker. A new synthesis is described starting from aldosterone 21‐acetate and the trichloroacetimidate of 2, 3, 4‐triacetylglucuronic acid methyl ester in the presence of TMSOTf, which is followed by two enzymatic steps. In this process also the novel C‐20‐glucuronides (2) are obtained. The so far unknown stereochemistry at C‐18 in (1) was determined by NOESY experiments.